2010
DOI: 10.1111/j.1939-165x.2010.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical and chemical immobilization on hematologic and biochemical variables in captive brown brocket deer (Mazama gouazoubira)

Abstract: Physical restraint and anesthesia affect some blood constituents in captive brown brocket deer, and midazolam premedication may modify the intensity of the stress response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…On the other hand, increase in serum cortisol concentration has also been observed in wild ungulates subject to stressful management events (Arzamendia et al 2010;Carmanchahi et al 2011;Nuvoli et al 2014). There are no cortisol values reported in a Dwarf Red Brocket, but the values detected in the present report are higher than previously reported for another species in this genus (Munerato et al 2010), corroborating that serum cortisol can be used as a stress indicator in the species.…”
Section: In Roe Deer Capreolussupporting
confidence: 81%
“…On the other hand, increase in serum cortisol concentration has also been observed in wild ungulates subject to stressful management events (Arzamendia et al 2010;Carmanchahi et al 2011;Nuvoli et al 2014). There are no cortisol values reported in a Dwarf Red Brocket, but the values detected in the present report are higher than previously reported for another species in this genus (Munerato et al 2010), corroborating that serum cortisol can be used as a stress indicator in the species.…”
Section: In Roe Deer Capreolussupporting
confidence: 81%
“…Studies about variations in blood values related to seasonality and nutrition (DeLiberto et al 1989, Rawson et al 1992, Barrozo et al 2001, Santana et al 2008, Gaspar--López et al 2011, Das et al 2012, Park et al 2012, sex and age (Jain 1997, Santos 1999, Thorn 2000, Santana et al, 2008, Rafaj et al 2011, Alhuay et al 2011) and type of capture method and stress (Mautz et al 1980, Fernández-Morán et al 2000, Munerato et al 2010) have being performed, but only a few with Mazama gouazoubira (Barrozo et al 2001, Santana et al 2008, Munerato et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Physical restraint in deer can lead to acute stress conditions, significantly increasing the total leukocytes in circulation due to catecholamine and glucocorticoid releases (Munerato et al 2010;Marco and Lavín 1999). Increased catecholamine and glucocorticoids result in lymphocyte destruction in the thymus cortex, stimulating the mobilization of neutrophils from the marginal pool to the circulation pool, prolonging neutrophil life in circulation, and affecting the higher ratio of neutrophils to lymphocytes (Kim et al 2005;Marco and Lavín 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Animal handling factors also have a significant role in measuring physiological values in deer. Several studies found that deer under chemical immobilization showed changes in physiological and hematological parameters (Munerato et al 2010;Topal et al 2010). Generally, the chemical restraint with anesthetics agents is widely chosen to minimize the acute stress condition in deer (Caulkeet and Arnemo 2014).…”
Section: Introductionmentioning
confidence: 99%